The pedagogical thought of Jose Marti in favour of the physical culture - Ramón Quevedo-Leguen; Odalis Frómeta-Rivera; Arelis Pérez-Asin (Universidad de Guantánamo, 2011)
The pedagogical thought of Marti is and will be a challenge for all educators if it is interest of them to apply to educational activity, but if he gives a correct application the success of its activity is assured, he will be preparing the man that the society demands: a man that thinks, acts, and has a good physical preparation for life. With encouraging results because it was verified it was proven that a teacher is able to participate actively in the different topics and more than a space of physical preparation, create as well debate and meditation about the benefits that they report for them.